2013
DOI: 10.1051/0004-6361/201220270
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-LAT andSuzakuobservations of the radio galaxy Centaurus B

Abstract: Centaurus B is a nearby radio galaxy positioned in the southern hemisphere close to the Galactic plane. Here we present a detailed analysis of about 43 months of accumulated Fermi-LAT data of the γ-ray counterpart of the source initially reported in the 2nd Fermi-LAT catalog, and of newly acquired Suzaku X-ray data. We confirm its detection at GeV photon energies and analyze the extension and variability of the γ-ray source in the LAT dataset, in which it appears as a steady γ-ray emitter. The X-ray core of Ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 71 publications
(105 reference statements)
2
24
0
Order By: Relevance
“…The analysis of gamma-ray data by Abdo et al (2010) and Yang et al (2012) has shown that the gammaray radiation emanating from Cen A's giant lobes is of inverseCompton origin, and that the lobes are particle dominated by a factor of a few. This is congruous with the results for the other two FR I galaxies resolved by Fermi-LAT, NGC 6251 (Takeuchi et al 2012) and Centaurus B (Katsuta et al 2013).…”
Section: Introductionsupporting
confidence: 82%
“…The analysis of gamma-ray data by Abdo et al (2010) and Yang et al (2012) has shown that the gammaray radiation emanating from Cen A's giant lobes is of inverseCompton origin, and that the lobes are particle dominated by a factor of a few. This is congruous with the results for the other two FR I galaxies resolved by Fermi-LAT, NGC 6251 (Takeuchi et al 2012) and Centaurus B (Katsuta et al 2013).…”
Section: Introductionsupporting
confidence: 82%
“…This table displays all the parameter values obtained and derived in and from the fit for the values of the distance d z = 56 Mpc, the viewing angle θ ≈ 20 • and the minimum electron Lorentz factor γ e,min = 100. The values shown in Table 3 are in the range of those reported by Katsuta et al [11]. The ratio between the magnetic field and electron density of U e /U B 200 indicates that these quantities cannot be associated to a mechanism of energy equipartition.…”
Section: The Region Close To the Coresupporting
confidence: 57%
“…The radio fluxes (green full circles) are taken from [5], [86] and [87]. The red bow tie and the thick black line correspond to the ASCA measurements [9] and the Suzaku upper limit [11] in the energy ranges of 0. δ=1.0 δ=1.5 δ=2.0 Figure 6. CR luminosity as a function of the target proton density within the extended lobes.…”
Section: A3 Hadronic Interactionsmentioning
confidence: 99%
“…Since 2009 the source has been observed about twice a year at 8 GHz, with one (quasi-)simultaneous observation at 22 GHz in (Müller et al, in prep.). From top left to bottom right: Parsecscale morphology of PKS 0235-618, one of the blazar sources consistent with one of the PeV neutrino events detected by IceCube (see Krauß et al 2014, for more details), the TeV-blazar PKS 0447-439, the flat-spectrum γ-ray quasar PKS 2142-758 (see Dutka et al 2013, for details on the multiwavelength properties), and the parsec-scale jet of the radio galaxy Centaurus B (PKS 1343-601) also detected at γ-rays (Katsuta et al 2013). The color scale displays the flux density distribution in mJy/beam.…”
Section: Vlbi Observationsmentioning
confidence: 83%